Increased Matrix Metalloproteinase 9 Activity in Mild Cognitive Impairment - Bruno, Martin A.; Mufson, Elliott J.; Wuu, Joanne; Cuello, A. Claudio (Journal of neuropathology and experimental neurology, 2009)
Nerve growth factor (NGF)-dependent cholinergic basal forebrain neurons degenerate during the progression of Alzheimer disease (AD). Elevated proNGF and reduced levels of the TrkA high-affinity NGF receptor occur in prodromal and advanced stages of AD. We recently described a protease cascade responsible for the conversion of proNGF to mature NGF (mNGF) in which matrix metalloproteinase 9 (MMP-9) degrades mNGF in the extracellular space. To determine whether this proteolytic cascade is altered during the progression of AD, we examined human frontal and parietal cortex tissues from aged subjects with a clinical diagnosis of AD, mild cognitive impairment, or no cognitive impairment. The analysis demonstrated greater MMP-9 activity in both AD and mild cognitive impairment compared with no cognitive impairment brain samples (p < 0.01), which supports the notion that a metabolic failure in the NGF-maturation/degradation pathway may be associated with an exacerbated degradation of mNGF in the cerebral cortex in early AD. Moreover, there were inverse correlations between Global Cognitive Score and Mini-Mental State Examination score and MMP-9 activity. These findings suggest that a reduction in mNGF as a consequence of MMP-9-mediated degradation may in part underlie the pathogenesis of cognitive deficits in mild cognitive impairment and AD.